Interpreting COVID-19 through the lens of the second Deep Transition - Schot, Johan (Ökologisches Wirtschaften - Fachzeitschrift, 2020)
Is COVID-19 a stepping stone towards a more sustainable future, or it is just a stone in the pond of which the effects will wither away as soon as we are back to normal? A look at the opportunities arising from the crisis.